2004
DOI: 10.1007/s00339-004-2856-y
|View full text |Cite
|
Sign up to set email alerts
|

Silicon clusters produced by femtosecond laser ablation: non-thermal emission and gas-phase condensation

Abstract: Neutral silicon clusters Sin (up to n = 7) and their cations Si + n (up to n = 10) have been produced by femtosecond laser ablation of bulk silicon in vacuum and investigated using time-offlight mass spectrometry. Two populations of the Si + n clusters with different velocity and abundance distributions in the ablation plume have been clearly distinguished. Possible mechanisms of cluster formation (Coulomb explosion, gas-phase condensation, phase explosion) are discussed.PACS: 52.38. MF; 61.46.+w; 79.20.Ds … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…For a more quantitative analysis of the ablation patterns, one will have to take the different coupling of normal and tangential field components into account. An improved understanding of the ablation processes induced by femtosecond pulses, which is still incomplete, 14 will also be required. On the other hand, the very local material removal taking place in the near-field of nanostructures might help to shed some light on the ablation mechanisms themselves.…”
mentioning
confidence: 99%
“…For a more quantitative analysis of the ablation patterns, one will have to take the different coupling of normal and tangential field components into account. An improved understanding of the ablation processes induced by femtosecond pulses, which is still incomplete, 14 will also be required. On the other hand, the very local material removal taking place in the near-field of nanostructures might help to shed some light on the ablation mechanisms themselves.…”
mentioning
confidence: 99%
“…There are still debates about ultrafast melting, 1-5 resolidification dynamics, [6][7][8] surface structure modification, 9,10 thermal and nonthermal mechanisms of ablation, 6,[11][12][13][14][15][16][17][18] and direct cluster emission. 16,[19][20][21] This stimulates extensive studies, both experimental and theoretical, of the dynamics of laser heating, melting, resolidification, and ablation of silicon under laser irradiation with different pulse durations and laser wavelengths. It has been shown that the silicon ablation mechanisms can be controlled by tailored laser pulses via governing the thermodynamic pathways of material evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, only the thermal energy translated from the friction force generated between surface atoms and surface neighboring atoms is delivered to the surface atoms. On the other hand, Si clusters are well known to evaporate by thermal processes such as laser irradiation [12,13] and simple annealing [14]. In these cases, the probability for emission of Si clusters is found to be extremely high, and the enhancement of the secondary cluster ion yields under the incidence of large cluster ions may be due to increased Si cluster emission probabilities through thermal processes.…”
Section: Resultsmentioning
confidence: 98%